SOSIALISASI BAITUL MAAL WA TAMWIL TERHADAP USAHA KECIL MENENGAH DAN PELAJAR SEKOLAH (Studi Kasus pada KSPPS BMT Pratama Cahaya Mentari Rawalumbu) - PUTI KHAIRANI RIJADI (DIRHAM Jurnal Ekonomi Islam, 2021)
Baitul Maal wat Tamwil (BMT) is a microfinance institution that operates based on profit sharing. Conceptually, BMT has two functions: to develop a productive business, and also to invest in improving the economic quality and small entrepreneurs. This study aims to determine the financial management of the KSPPS PCM Rawalumbu. The method used qualitative data analysis based on the results of questionnaires. The results of this study indicate that the KSPPS PCM Rawalumbu, which was just born on November 25th, 2020, currently, has 70 (seventy) members, consisting of cooperative members and ordinary members. However, the financial support of this KSPPS still needs support from the Head of Muhammadiyah Rawalumbu (Pimpinan Cabang Muhammadiyah/PCM Rawalumbu) because it was just recently established. Financing lending still for consumptive needs (such as laptops, motorbikes, etc). However, it has met the adequacy of business needs, and the profit-sharing has also been in accordance with the existing agreement.